Rhinofacial entomophthoramycosis; a case series and review of the literature - Juvady Leopairut (2018)
Rhinofacial entomophthoramycosis is an uncommon chronic mycotic disease caused by exposure to the organism Conidiobolus coronatus. The authors report a case series of 5 patients with rhinofacial entomophthoramycosis and review the literature. All patients had typical involvement of the rhinofacial area with formation of subcutaneous lesions causing a chronic granulomatous inflammatory response with tissue eosinophilia and Splendore-Hoeppli reaction. Diagnoses were made based on histopathologic examination in all cases and fungi were isolated and identified in one case. The clinicopathologic features and therapeutic management of rhinofacial entomophthoramycosis are described.